Effect of Analytical Particle Size on Pore Structure of High Volatile Bituminous Coal and Anthracite Using Low-Pressure N2 and CO2 Adsorption - Zheng Dang; Xiaoming Wang; Shihui Hou; Sidong Pan (Adsorption Science & Technology)
To investigate the effect of analytical particle size on pore structure, mesopore (2-50 nm) and micropore (<2 nm) characteristics of high volatile bituminous coal and anthracite with different particle size were determined using low-pressure N2/CO2 adsorption analyses. Mesopore structure parameters in the two coals increase with decreasing particle size, which are attributed to the opening of closed mesopores during the pulverization process. The closed mesopores with different pore size ranges are opened with a certain percentage in high volatile bituminous coal, but opened irregularly in anthracite during pulverization. Micropore structure parameters of the two coals show different variations with decreasing particle size, which are not related to the reconstituted micropore structure. Mineral matter contributes more mesopores than organic matter in anthracite and exerts the negative effect on micropore in the two coals. An evolution model is established to elaborately describe the change of pore structure during the pulverization process, where mineral matter plays a mediating role in the effect of particle size on pore structure.